The Influence Of Leadership Style, Knowledge Management, And Organizational Culture On Employee Performance on SME’s - Fitrilia, Aziza Daning; Murniningsih, Rochiyati; Santosa, Mulato; Zuhriyah, Eni (Prosiding University Research Colloquium, 2022)
This study aims to examine the influence of leadership style, knowledge management and organizational culture on employee performance at the UMKM Tahu Mejing Village. The population in this study were the employees of SMEs Tahu Mejing Village, Candimulyo District, Magelang Regency. The sample taken in this study were 76 employees with purposive sampling method. The analytical tool used is multiple linear regression. The results showed that leadership style had a positive and significant effect on employee performance, knowledge management had a positive and significant effect on employee performance and organizational culture had a positive and significant effect on employee performance.